2018
DOI: 10.1038/s41598-018-22760-5
|View full text |Cite
|
Sign up to set email alerts
|

Azolla along a phosphorus gradient: biphasic growth response linked to diazotroph traits and phosphorus-induced iron chlorosis

Abstract: Azolla spp., a water fern often used for phytoremediation, is a strong phosphorus (P) accumulator due to its high growth rate and N2 fixing symbionts (diazotrophs). It is known that plant growth is stimulated by P, but the nature of the interactive response of both symbionts along a P gradient, and related changes in growth-limiting factors, are unclear. We determined growth, and N and P sequestration rates of Azolla filiculoides in N-free water at different P concentrations. The growth response appeared to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…As suggested by Brouwer et al (2018), regular harvests of Azolla can be used to maintain cultures in a linear growth phase and to obtain predictable and high biomass yields. Our results confirm that the biomass production of Azolla depends on fertilizer concentrations and presumably by P concentrations because this nutrient is the most limiting in Azolla culture (Subudhi and Watanabe, 1981;Kushari and Watanabe, 1991;Temmink et al, 2018). Although production varied with environmental conditions (light and temperature), productivity remained high (median values: 44, 73 and 79 g FW m -2 d -1 for Azolla maintained under a shade net, clear plastic or exposed to direct sunlight, respectively) 15 when plants were cultivated at high fertilizer concentrations (addition of 16, 10 and 7.5 µmol L -1 of N, P and K respectively), regardless of the environmental conditions.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…As suggested by Brouwer et al (2018), regular harvests of Azolla can be used to maintain cultures in a linear growth phase and to obtain predictable and high biomass yields. Our results confirm that the biomass production of Azolla depends on fertilizer concentrations and presumably by P concentrations because this nutrient is the most limiting in Azolla culture (Subudhi and Watanabe, 1981;Kushari and Watanabe, 1991;Temmink et al, 2018). Although production varied with environmental conditions (light and temperature), productivity remained high (median values: 44, 73 and 79 g FW m -2 d -1 for Azolla maintained under a shade net, clear plastic or exposed to direct sunlight, respectively) 15 when plants were cultivated at high fertilizer concentrations (addition of 16, 10 and 7.5 µmol L -1 of N, P and K respectively), regardless of the environmental conditions.…”
supporting
confidence: 80%
“…100 g FW m −2 and surface cover of ~20%). Plants were acclimated for 11 days without harvesting to minimize P history effects (Temmink et al, 2018). During the experiment, water in drums was changed 6 times per week.…”
Section: Experiments 1: Effects Of Shading Materials and Fertilization On Azolla Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh weight, RGR and dry weight of A. pinnata were enhanced by the supplementation of P and were maximum (5.01 kg/m 2 , 0.82 g/g per day and 0.25 kg/m 2 , respectively) with 10 ppm P. De et al (2015) observed that under P depletion, A. pinnata had recorded a significant restriction of growth by dry matter loss. Temmink et al (2018) in a laboratory experiment observed significant increase in RGR in A. filiculoides, when culture medium was supplied with 0.3 ppm P and further increase in P up to 10 ppm could not improve the RGR. Gerek (2001) reported that 1122 g/m 2 of fresh Azolla mexicana can be harvested after15 days with the initial fresh weight of 300 g/m 2 of Azolla.…”
Section: Resultsmentioning
confidence: 93%
“…Adding fertilizers to Azolla sp . enhances its nutrition value [ 38 ]. Moreover, it can be used as a biological filter for purifying water as well as providing food and shelter to fish and invertebrates [ 39 ].…”
Section: Introductionmentioning
confidence: 99%